Targeting tumor metabolism to augment CD8+ T cell anti-tumor immunity - Huan Liu; Wenyong Yang; Jingwen Jiang (Journal of Pharmaceutical Analysis)
CD8+ T cell-based immune-therapeutics, including immune checkpoint inhibitors and adoptive cell therapies (tumor-infiltrating lymphocytes (TILs), T cell receptor-engineered T cells (TCR-T), chimeric antigen receptor T cells (CAR-T)), have achieved significant successes and prolonged patient survival to varying extents and even achieved cure in some cases. However, immunotherapy resistance and tumor insusceptibility frequently occur, leading to treatment failure. Recent evidences have highlighted the ponderance of tumor cells metabolic reprogramming in establishing an immunosuppressive milieu through the secretion of harmful metabolites, immune-inhibitory cytokines, and alteration of gene expression, which suppress the activity of immune cells, particularly CD8+ T cells to evade immune surveillance. Therefore, targeting tumor cell metabolic adaptations to reshape the immune microenvironment holds promise as an immunomodulatory strategy to facilitate immunotherapy. Here, we summarize recent advances in the crosstalk between immunotherapy and tumor reprogramming, focusing on the regulatory mechanisms underlying tumor cell glucose metabolism, amino acid metabolism, and lipid metabolism in influencing CD8+ T cells to provide promising metabolic targets or combinational strategies for immunotherapy.